2022
DOI: 10.1038/s41598-022-21289-y
|View full text |Cite
|
Sign up to set email alerts
|

New symptoms and prevalence of postacute COVID-19 syndrome among nonhospitalized COVID-19 survivors

Abstract: The aim of this study was to assess postacute coronavirus disease 2019 (COVID-19) syndrome (PACS) symptoms according to the onset of the infection while evaluating the effect of COVID-19 vaccination on the symptoms of PACS. We conducted a retrospective single-center cohort study in which nonhospitalized COVID-19 survivors and healthy controls were compared for the occurrence of PACS. The total number of patients in this study was 472. At 6–12 and > 12 months after the infection, COVID-19 survivors had a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
1
1
0
1
Order By: Relevance
“…Multivariate analyses suggested that greater Long COVID symptom burden was associated with older age, female sex, as well as poorer self-appraised health prior to having COVID-19 and being hospitalized for COVID-19. Our findings are in general agreement with existing reports [ 18 , 28 , 29 , 30 , 31 , 32 , 33 ]. These results can inform clinicians to help identify patients at increased risk for Long COVID-related medical issues, as well as be used by health systems to manage operational expectations on a population-health level as there are implications for the application to clinical screening programs geared toward these specific patients [ 34 ].…”
Section: Discussionsupporting
confidence: 94%
“…Multivariate analyses suggested that greater Long COVID symptom burden was associated with older age, female sex, as well as poorer self-appraised health prior to having COVID-19 and being hospitalized for COVID-19. Our findings are in general agreement with existing reports [ 18 , 28 , 29 , 30 , 31 , 32 , 33 ]. These results can inform clinicians to help identify patients at increased risk for Long COVID-related medical issues, as well as be used by health systems to manage operational expectations on a population-health level as there are implications for the application to clinical screening programs geared toward these specific patients [ 34 ].…”
Section: Discussionsupporting
confidence: 94%
“…To date, the occurrence of COVID-19-related anxiety, depression, and PTSD in non-hospitalized patients (Albtoosh et al, 2022 ), non-critically ill hospitalized patients (Mazza et al, 2023 ; Yunitri et al, 2022 ) and critically ill hospitalized patients (Groff et al, 2021 ; Nagarajan et al, 2022 ; Sankar et al, 2023 ; Yang et al, 2022 ; Zürcher et al, 2022 ) has been extensively described in several systematic reviews and meta-analyses. However, in these studies, the data have been analysed for each disorder separately, or by grouping them into a single mental health category, without an in-depth consideration of the specific overlap between depression and PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…7 La prevalencia de estos síndromes disminuye con el tiempo, es del 10% tras 12 años de seguimiento, 105 y se caracterizan por empeorar la calidad de vida de los pacientes. 119 Esto tiene especial relevancia en una patología como la COVID-19 si tenemos en cuenta el número de pacientes infectados a nivel mundial y que ni los ambulatorios 226,227 ni los vacunados 120 están exentos de desarrollarlos. Se estima que la prevalencia de este síndrome post-COVID es mayor del 10%, 110,226 La fatiga, 106,109,111,112,128 las secuelas pulmonares y las neuro-psiquiátricas son los hallazgos más comunes.…”
Section: Anomalías Funcionales Durante El Seguimientounclassified